2013
DOI: 10.1097/tp.0b013e3182943506
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Effect of Preformed Anti-MICA Antibodies on Renal Allograft Evolution in Early Posttransplantation Period

Abstract: Pretransplantation sensitization against MICA and HLA are independent events. Preformed anti-MICA antibodies independently increase risk for kidney rejection and enhance the deleterious effect of PRA+ status early after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…In a more recent and large cohort study, Sánchez‐Zapardiel et al. also showed that in patients without anti‐HLA antibodies, pre‐transplantation anti‐MICA antibodies significantly increased the rejection rate at 3 and 6 months (p = 0.032, 0.046). To summarize, it is not clear whether MICA antibodies are associated with allograft survival, and more studies are required (Table ).…”
Section: Mica In Renal Transplantationmentioning
confidence: 94%
“…In a more recent and large cohort study, Sánchez‐Zapardiel et al. also showed that in patients without anti‐HLA antibodies, pre‐transplantation anti‐MICA antibodies significantly increased the rejection rate at 3 and 6 months (p = 0.032, 0.046). To summarize, it is not clear whether MICA antibodies are associated with allograft survival, and more studies are required (Table ).…”
Section: Mica In Renal Transplantationmentioning
confidence: 94%
“…We retrospectively analysed 727 consecutive kidney allograft recipients transplanted between 2005 and 2011 in our hospital (cohort previously described [10]). The study was performed under informed consent and approved by the institutional review board (reference 10/014).…”
Section: Patients and Samplesmentioning
confidence: 99%
“…Anti-MICA-specific antibody and C1q binding assays Anti-MICA-positive samples in the screening test [10] were tested by Luminex ® for individual anti-MICA specificities [Luminex single-antigen (LSA) assay, LABScreen MICA Single Antigen kit, One Lambda, Canoga Park, CA, USA]: 001, 002, 004, 007, 009, 012, 015, 017, 018, 019 or 027. C1q binding was tested in LSA-positive samples with the C1qScreen™ kit.…”
Section: Patients and Samplesmentioning
confidence: 99%
See 2 more Smart Citations